UPAYA PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN LANGSUNG MATA PELAJARAN MATEMATIKA KELAS VIII-4 SMPN 1 NAMORAMBE - Firman Immanuel (Universitas Negeri Medan, 2016)
Abstract: Measures For Enhancing Activities Student Learning Through Direct Application As Learning Model Subject In Math Class VII-4 SMPN 1 Namorambe. The study aims to look at the activity and student achievement. The research subject VIII-4 with the number of students 35 people. Activities in the first cycle read / write (42%), work (27%), ask peers (5.3%), ask the teacher (14.2%), and are not relevant to KBM (12%). Activities in the second cycle read / write (25.6%), work (52.5%), asked their peers (14.4%), ask the teacher (3%), and are not relevant to KBM (4.4 %). Pretest with an average of 32.0. On Formative first 23 students completed. In the second cycle, completed 31 students, with an average cycle I and II are 68.57 and 85.14 with a percentage of 65.71% and 87.56%. Keywords: Direct Learning Model, Learning Activities, Results Learn math. Abstrak: Upaya Peningkatan Belajar Siswa Melalui Model Pembelajaran Langsung Mata Pelajaran Matematika Kelas VII-4 SMPN 1 Namorambe. Penelitian bertujuan untuk melihat aktivitas dan prestasi belajar siswa. Subjek penelitian kelas VIII-4 dengan jumlah siswa 35 orang. Aktivitas pada siklus I membaca/menulis (42%), bekerja (27% ), bertanya sesama teman (5,3%), bertanya kepada guru (14,2%), dan yang tidak relevan dengan KBM (12%). Aktivitas pada siklus II membaca/menulis (25,6%), bekerja (52,5%), bertanya sesama teman (14,4%), bertanya kepada guru (3%), dan yang tidak relevan dengan KBM (4,4%). Pretes dengan rata-rata 32,0. Pada Formatif I 23 orang siswa tuntas. Pada Siklus II, tuntas 31 orang siswa, dengan rata-rata siklus I dan II adalah 68,57 dan 85,14 dengan presentase 65,71% dan 87,56%. Kata Kunci : Model Pembelajaran Langsung, Aktivitas Belajar, Hasil Belajar, Matematika.